2015
DOI: 10.1016/j.antiviral.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Immune-modulators to combat hepatitis B virus infection: From IFN-α to novel investigational immunotherapeutic strategies

Abstract: Chronic hepatitis B virus (HBV) infection remains a major challenge for clinicians, as there are only two types of approved therapies: interferon-alpha (IFN-α) or its pegylated form, Peg-IFN-α and nucleoside analogs (e.g. tenofovir, entecavir...). The first are used as finite-duration treatments of around 48-52 weeks, while the second must be taken life-long to prevent rebound. Other immune-modulators, including other types of recombinant IFNs and cytokines/chemokines, could be developed for treating chronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 106 publications
0
49
0
Order By: Relevance
“…Current treatments for chronic hepatitis B include type I interferons for a fraction of the patients [11], and the better tolerated nucleos(t)ide analogs (NAs) inhibiting reverse transcription for the majority [12]. Either therapy may achieve control of infection but rarely leads to a cure because cccDNA is not directly targeted; even after recovery from acute self-limited hepatitis B cccDNA is not completely eliminated [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments for chronic hepatitis B include type I interferons for a fraction of the patients [11], and the better tolerated nucleos(t)ide analogs (NAs) inhibiting reverse transcription for the majority [12]. Either therapy may achieve control of infection but rarely leads to a cure because cccDNA is not directly targeted; even after recovery from acute self-limited hepatitis B cccDNA is not completely eliminated [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large body of evidence has shown that many IFNs/cytokines, including IFN-α, IFN-γ, IFN-β, IFN-λ, IL-6, TNF-α, and IL-1β were capable of inhibiting HBV replication in hepatocytes, in the absence of immune cells [78,79,100,107]. These innate effectors are capable of inhibiting the transcription of cccDNA (thought to be through distinct molecular mechanisms; unpublished data), and some of them are also capable of inducing the degradation of cccDNA in vitro, as initially shown with LT-βR agonists, which were particularly potent in this respect [100].…”
Section: Interplay Between Hbv and Innate Immunity: Therapeutic Inmentioning
confidence: 99%
“…If the stimulation of immune cells capable of locally and temporally producing either IFN-α (via pDC), IFNs-λ (via BDCA3 + cells) or IL-1β (via myeloid cells), which have direct anti-HBV properties [107], which is a sound approach theoretically, and could be achieved for instance by PRR agonists, a cell-therapy based on pDC or BDCA3 + DC loaded with HBV-derived peptides could also be an interesting approach. Indeed, these cells could both produce cytokines and elicit T-cell functions via their APC properties.…”
Section: Interplay Between Hbv and Innate Immunity: Therapeutic Inmentioning
confidence: 99%
“…HBV has been shown to downregulate TLR2 expression in patients with chronic HBV infection [66] . Thus, innate immunity alteration plays a role, at least in part, in the pathogenesis of chronic HBV infection and TLR7 agonists have been applied as immunemodulatory components [67,68] . On the other hand, the effect of IFNα on intrahepatic cccDNA has been recently explored [69] , and IFNα in addition to lymphotoxinβ receptor (LTβR) activation has been shown to induce cccDNA degradation through upregulation of nuclear APOBEC3 deaminases [70] .…”
Section: Impairment Of Innate Immune Responsementioning
confidence: 99%
“…Other immunotherapeutic approaches to HBV infec tion include administration of cytokines, such as IFNγ, IL6, IL1β, LTβRagonists and/or TLR7 agonist, as well as IFNγ and TNFα which were shown to cause silencing or degradation of cccDNA [67] . This strategy may be more effective in the complete eradication of HBV infection than strategies involving the activation of HBVspecific cells, suggesting that only cytokine administration results in the elimination of cccDNA.…”
Section: Induction or Stimulation Of Hbv-specific Immune Responsesmentioning
confidence: 99%